The formulation of nusantara fiqh in Indonesia - M. Noor Harisudin (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2021)
This article discusses how Fiqh Nusantara, an Islamic jurisprudence in Indonesia was formed and formulated.  Data were obtained through library research, classic literature commonly used in Islamic boarding schools, fatwas of the Indonesian Council of Ulama, Nahdlatul Ulama, and Muhammadiyah. The Fiqh Nusantara contextualization in Indonesian locus – known as Fiqh Nusantara– is posed from distinctive genealogy and characteristics compared to Fiqh that has developed in the Middle East. One of the characteristics of Fiqh Nusantara is that it has strengthened the unity of the Republic of Indonesian as indicated by its various contributions in the national legal system. Additionally, it has been resulted in a dialogical process in which many fatwas developed and lived in the community. It is responsive to recent developments of fiqh and it is not derived from one school of thought. It is created through collective efforts (collective ijtihad) in the form of fiqh which is open to variety of opinions. However, Fiqh Nusantara as an Islamic law in Indonesia has not yet penetrated the domain of mahdlah (sincere worship to the God). For Fiqh Nusantara activists, it was only applicable to the changing domain of fiqh (mutaghayirat) and not to the fixed domain of fiqh (tsawabit).